Oracle database 11g PL/SQL programming [ - McLaughlin, Michael [ (Michael J.)] (McGraw-Hill, 2008)
"Deliver dynamic, client/server PL/SQL applications with expert guidance from an Oracle programming professional. With full coverage of the latest features and tools, Oracle Database 11g PL/SQL Programming lays out each topic alongside detailed explanations, cut-and-paste syntax examples, and real-world case studies. Access and modify database information, construct powerful PL/SQL statements, execute effective queries, and deploy bulletproof security. You'll also learn how to implement C, C++, and Java procedures, Web-enable your database, cut development time, and optimize performance."--BOOK JACKET